2001
DOI: 10.1046/j.1365-3016.2001.0380a.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions during pregnancy in two urban areas of Ukraine

Abstract: Hospital admissions are generally regarded as a marker of severe pregnancy complications, and a low ratio of antenatal admissions to deliveries is considered an indicator of maternal-fetal well-being. We investigated the reasons for hospital admissions in a sample of deliveries from Ukraine, a country of the former eastern bloc. All hospitalisations were traced among 3099 women who delivered live singletons of at least 20 weeks gestation in two urban areas of Ukraine and data were abstracted from their medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A study carried out in Ukraine found a 52% rate of hospital admissions due to complications during pregnancy in relation to childbirth (12) . The most frequent and severe complications are those of labor and delivery that reach 31.2 per every 100 births in the United States (13) .…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Ukraine found a 52% rate of hospital admissions due to complications during pregnancy in relation to childbirth (12) . The most frequent and severe complications are those of labor and delivery that reach 31.2 per every 100 births in the United States (13) .…”
Section: Discussionmentioning
confidence: 99%